Improving strategic planning: The crucial role of enhancing relationships between management levels - Daniel Mandel Gandrita (Administrative Sciences, 2023)
Having a fruitful relationship with all levels of management can increase the likelihood of better opportunities within and outside the organization. In some environments, it is known that participation in strategic planning creates better overall conditions for all partners, better conditions for retention, and above all, loyalty to talent. The very acceptance of contributions to this desideratum entails knowledge sharing and knowledge management. Our study examines how the relationship between management levels can disrupt strategic planning, particularly in contexts of resistance to change, situations that can affect talent retention and loyalty. Gathering the essential data to enhance the recommendations and contributions, the organization's overall robustness takes shape through a combination of participant and nonparticipant observation, alongside interviews and questionnaires administered within the company. Initially, a qualitative approach was employed, involving interviews with a cohort of n = 14 top management executives. Subsequently, a qualitative method was employed, involving questionnaires distributed to a group of n = 204 individuals encompassing middle and lower management levels. Our conclusions, therefore, reflect the continuation of a research study. This paper contributes to the literature of work pursued by exploring how social actors and different stakeholders can make a difference in participating in strategic planning and how they can overcome, in counterpoint, the limitations of possibly not being able to participate in such strategic planning. Our contribution will also result in a critical understanding of the need for talent retention and loyalty, highlighting how retention efforts, especially the small nudges that are absolutely significant in terms of employee participation and even emotional pay purposes, are differentiators and can overcome, very concretely, resistance to change.
Keywords: 350; improvement; management levels; management roles; performance; retainment; strategic planning